2019
DOI: 10.1002/mds.27642
|View full text |Cite
|
Sign up to set email alerts
|

SMPD1 mutations, activity, and α‐synuclein accumulation in Parkinson's disease

Abstract: Background SMPD1 (acid‐sphingomyelinase) variants have been associated with Parkinson's disease in recent studies. The objective of this study was to further investigate the role of SMPD1 mutations in PD. Methods SMPD1 was sequenced in 3 cohorts (Israel Ashkenazi Jewish cohort, Montreal/Montpellier, and New York), including 1592 PD patients and 975 controls. Additional data were available for 10,709 Ashkenazi Jewish controls. Acid‐sphingomyelinase activity was measured by a mass spectrometry‐based assay in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 34 publications
4
106
3
Order By: Relevance
“…Interestingly, variants in the gene encoding sphingomyelinase are also risk factors for PD. 15 In this study, urinary di-18:1-BMP and di-22:6-BMP and their 2,2 0 isoforms were elevated in LRRK2 G2019S mutation carriers (with and without PD), compared with noncarriers. In contrast, mice with germline deletion of LRRK2 and cynomolgus monkeys treated with 3 distinct LRRK2 kinase inhibitors show decreases in urinary di-22:6-BMP levels.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Interestingly, variants in the gene encoding sphingomyelinase are also risk factors for PD. 15 In this study, urinary di-18:1-BMP and di-22:6-BMP and their 2,2 0 isoforms were elevated in LRRK2 G2019S mutation carriers (with and without PD), compared with noncarriers. In contrast, mice with germline deletion of LRRK2 and cynomolgus monkeys treated with 3 distinct LRRK2 kinase inhibitors show decreases in urinary di-22:6-BMP levels.…”
Section: Discussionmentioning
confidence: 52%
“…Both di‐18:1‐BMP and di‐22:6‐BMP are elevated in patients with Niemann‐Pick disease, a lysosomal disorder caused by diminished acid sphingomyelinase levels. Interestingly, variants in the gene encoding sphingomyelinase are also risk factors for PD …”
Section: Discussionmentioning
confidence: 99%
“…Some forms of ceramide in the plasma of PD patients are higher in individuals with dementia when compared with nondemented patients . In addition, mutations in the SMPD1 gene that encode sphingomyelinase is correlated with an increased risk of PD . Mutations in the GBA gene that encodes glucocerebrosidase, which produces ceramide from glucocerebroside, are also associated with PD .…”
Section: Contributions From the Basic Sciencesmentioning
confidence: 99%
“…81,82 In addition, mutations in the SMPD1 gene that encode sphingomyelinase is correlated with an increased risk of PD. [83][84][85][86][87][88] Mutations in the GBA gene that encodes glucocerebrosidase, which produces ceramide from glucocerebroside, are also associated with PD. 89,90 In the lysosome, sphingomyelinase and glucocerebrosidase hydrolyze sphingolipids to produce ceramide.…”
Section: Glucose Lipid and Cholesterol Metabolismmentioning
confidence: 99%
“…aSMase belongs to the sphingomyelinase family, responsible for catalyzing the breakdown of sphingomyelin to Cer and phosphorylcholine. A recent study showed that reduced aSMase activity in blood samples is associated to a 3.5‐ to 5.8‐year earlier onset of PD …”
Section: The Issue Of Alp Alterations In Sporadic Pdmentioning
confidence: 99%